Analisis Pendapatan Usahatani Lada Sebelum dan Sesudah Menerima Kredit Usaha Rakyat (KUR) di Desa Ulusena Kecamatan Moramo Kabupaten Konawe Selatan - Aditia, Rudi; Bafadal, Azhar; Indarsyih, Yusna (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
This research based on by the pepper plants that became one of the good commodities in Southeast Sulawesi, South Konawe regencies in Southeast Sulawesi. South Konawe is one of the regencies in Southeast Sulawesi which cultivate the plants of pepper, pepper plant needs a financial capital. There are two sources of financial capital in planting the pepper, first the financial capital private and secondly the loan capital, loan capital comes from a wholesaler and from financial institutions (banks). The purpose of the study to analyze the difference of income before and after receiving Kredit Usaha Rakyat (KUR) in the village of Ulusena sub-district of Southeast Konawe. The decision of choosing the location of research is considered by the community of farmers which planting pepper is their main livelihood and take Kredit Usaha Rakyat (KUR) from BRI. The number of respondents is 37 farmers pepper. The data analysis use analysis of income, and the t-test (paired simple past test). The research results showed that the income of farming pepper before receive KUR is amounting to Rp 1,257,394,000 and the income of farming after KUR Rp 1,780,746,000. The t-test analysis results (paired test) showed that there is significant revenue which differences between farming pepper before and after receiving a Kredit Usaha (KUR).